FOREST COVER CHANGE DETECTION IN PAKTIA PROVINCE OF AFGHANISTAN USING REMOTE SENSING AND GIS: 1998-2018 - Mujeeburahman Ariez; Khanzad Gul zazai; Mohammad Ismael Larwai; Akhlaq Amin wani (Forestry Study Program University Of Mataram, 2022)
Monitoring changes in forest cover is important to address issues like biodiversity conservation, sustainable management, and climate change. The study has been conducted in the Paktia province of Afghanistan to assess the changes in different forest classes which occurred together with political changes by using Remote Sensing and Geographic Information System (GIS). The change was analyzed for a period of two decades, i.e., 1998 to 2018. Landsat TM and OLI satellite images of 30m resolution for the years 1998 and 2018 were used respectively. The overall classification accuracy of the mapping was estimated as 82.67% and the kappa coefficient was estimated as 0.8081. The study area was delineated via visual image interpretation technique into 11 LULC classes’ viz., closed forest, open forest, forest scrub, grassland other classes (Agriculture, Agroforestry, horticulture, habitation, waterbody, wasteland, and snow). The comparison of maps 1998 and 2018 revealed that the total area under closed forest, open forest, showed an increase of 0.43%, 0.73%, respectively. While the areas under forest scrub, showed a decline of 0.30%, during the study period (1998-2018).